Empirical Examination on the Drivers of the U.S. Equity Returns in the During the COVID-19 Crisis - Wang, Qing; Bai, Mo; Huang, Mai (Frontiers in Public Health, 2021)
This study investigates the drivers of the Standard & Poor's (S&P) 500 equity returns during the COVID-19 crisis era. The paper considers various determinants of the equity returns from December 31, 2019, to February 19, 2021. It is observed that the United States Dollar (USD) and the Volatility indices (VIX) negatively affect the S&P 500 equity returns. However, the newspaper-based infectious disease "equity market volatility tracker" is positively associated with the stock market returns. These results are robust to consider both the Ordinary Least Squares (OLS) and the Least Angle Regression (LARS) estimators.